PENERAPAN KEGIATAN PEMBELAJARAN IPA BERBASIS STEM DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA DAN PENGUASAAN KONSEP GERAK LURUS DI SMP - Lintang Nurul Fatichah, - (2019)
Developments in science and technology is growing seiringnya increasing time. The development of technology and science in the age of globalization can provide very significant benefits for human life. In this globalization era, perkembagan science and technology can require people to be able to hone the ability to think creatively and human skills in order to compete not only national but the scope of international scope. In this 21st century, one of the ways to be competitive in the international scope is to improve the quality of education. In this 21st century education is important for everyone, for the education of every individual will benefit and grow well if it can be used in a competent manner. In the world of education, STEM-based science learning is often used during the learning process. STEM-based science learning is an approach to science teaching that the learning process that integrate the four disciplines of science, technology, engineering, and mathematics. Therefore, this study aims to determine the increase mastery of concepts and students' motivation by using STEM-based science learning. This study uses a one-group pretest-posttest design with a participation rate of 28 students Junior High School in Bandung. The instrument used in this study in the form of multiple choice questions and learning motivation questionnaire on aspects Need for Achievement, Need for Power aspects, and aspects of the Need for Affiliation.